Climate risks, regional integration and sustainability in the Mekong region - Lebel L; Hoanh, Chu Thai; Krittasudthacheewa, C.; Daniel, R. (Strategic Information and Research Development Centre (SIRDC) and SUMERNET Stockholm Environment Institute (SEI), 2014)
The book brings together multi-country empirical case studies, each of which included significant engagement with boundary partners, to analyse the impacts of, and ways to adapt to, climate risks and unsustainable growth in a highly interdependent region. Rapid economic growth coupled with current and projected climate risks are challenging livelihoods and ecosystems in the Mekong Region. In some locations unsustainable development has created or deepened vulnerabilities to climate change as well as global, regional, and transborder socioeconomic processes. More accessible and appropriate information is urgently needed on ways to reduce the negative aspects of development and adapt to the impacts of climate change in this region.